Desain dan Implementasi Sistem Kendali CNC Router Menggunakan PC untuk Flame Cutting Machine - Roni Permana Saputra; Anwar Muqorobin; Arif Santoso; Teguh Pudji Purwanto (National Research and Innovation Agency, 2011)
This paper focuses on design of router control systems based on computer numerical control (CNC) using personal computer (PC) implemented in flame cutting machine (FCM). NC-Code entered into the computer translated to be a command signal sent by the PC to a microcontroller to control the end effector’s movement alongthe X and Y axis simultaneously based on linear and circular interpolations calculation on the PC. This control system is implemented on FCM by connecting the output control of the microcontroller with the driver actuator of the FCM in the form of a DC motor. The obtained result is in the form of a CNC router control system prototype to be implemented in the FCM which is capable to perform linear interpolation and circular interpolation.